We have 2 fractions with a common denominator 0f 3x.
14/(3X) + (X+5)/(3X)=(14 + (X+5)) / 3X
= (14 + X + 5) / 3X = (X+19) / 3X.
Simplify the expression: 14/(3x) + (x+5)/(3x)
2 answers
Set the expression equal to zero, then subtract (x+5)/(3x) from both sides:
14/(3x)=-(x+5)/(3x)
Then multiply 3x to both sides to eliminate that value completely. So you're left with:
14=(x+5)
Then just solve for x.
14/(3x)=-(x+5)/(3x)
Then multiply 3x to both sides to eliminate that value completely. So you're left with:
14=(x+5)
Then just solve for x.